Diseño de mobiliario para laboratorios de computación de la Facultad de Diseño y Arquitectura de la Universidad Técnica de Ambato - Proaño Villacrés, Caroline Michelle (2024)
The (OMS) states that (TME) are multifactorial health conditions, which implies that their development is influenced by various risk factors. The discipline of human computer interaction stands as a crucial field of research that seeks to mitigate the challenges that people face when interacting with technological devices. It is vital to understand user needs and perform a thorough analysis to select the most appropriate product architectures. This approach becomes even more critical when considering the relationship between technology and users' body postures, especially in environments such as computer laboratories. In the Ecuadorian context, with 60 universities and polytechnic schools, the problem focuses on computer laboratories, especially in public institutions supported by Senescyt. These share furniture that does not comply with adequate measures, representing a long-term health risk. The lack of ergonomic furniture is related to cardiac and musculoskeletal problems, according to research by the IESS between 2015 and 2017, where musculoskeletal disorders constitute 87% of pathologies. By proposing an attractive, comfortable and functional furniture proposal, it is presented as a solution that positively impacts people's attitude towards the care of equipment. A well-designed and pleasant work environment fosters a sense of belonging and respect for available resources. By aesthetically appreciating furniture, users are motivated to protect both furniture and equipment, thus promoting active learning